EFEKTIFITAS METODE SHOW AND TELL DALAM KEMAMPUAN BERPIDATO BERDASARKAN GENDER DI SEKOLAH DASAR - Mayang Adinda Wulandari; Vevy Liansari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was carried out because of the low speaking skills of students in learning Indonesian speech. Speech includes gestures, vocabulary, voice intonation, pronunciation, facial expressions. This research aims to determine the effectiveness of the show and tell method in speech abilities based on gender. The researcher uses the show and tell method as an action that will be given to students. This show and tell method involves students directly so that students are free to express themselves and channel their thoughts. The population taken by researchers is all 26 class V A students. This research has type of Pre Experimental Design research with a oneshot study research design.The data analysis technique uses the t test with a significance level of α= 0,05. It was concluded that there was effectiveness of the show and tell method in speech abilities based on the gender of class V students at SDN Sepande. Based on calculations, the results of the average posttest value are greater than the results of the average pretest value. In this way, the show and tell method can improve the speech skills of class V students at Sepande Elementary School.